Speech Act Of Promising Used By Pacitan Vocational English Teacher - Karyono, Joko; , Agus Wijayanto, Ph.D; , Dr. Anam Sutopo, M.Hum (2015)
Communication plays an important role in human life. To communicate people need a language to express their ideas and feelings because the primary function of the language is as a means of communication. The focus of the study is on the pragmatic analysis of the speech act of promising used by Pacitan Vocational English teacher. Speech act study in various languages and perspectives could help conecting the gap among the speakers ofdifferent languages i.e. help to inform and prepare speakers of the possible pragmatic failures that may arise in social, pedagogical and translation domains. These studies also may help speakers of dissimilar languages and cultures manage with interethnic communication difficulties. This article presents a study on speech acts that aims to fill the above-mentioned gap. This particular research, however, concentrates on the analysis of the strategies of promising and what dominat strategy used by Pacitan Vocational English teacher and also what pragmalinguistics form used in delivering the promise. The data source of this study is document. The document are taken from Vocational English teachers in Pacitan. The data source is taken by the purposive criterions based on the situation presnted in the DCT. The analysis reveals that the respondents applied performative and non performative verb in stating the promises. The dominant promising strategy used by the teachers is promising non performative verb. Moreover,there are seventen pragmalinguistics form used by the respondents.